1996
DOI: 10.1073/pnas.93.14.7381
|View full text |Cite
|
Sign up to set email alerts
|

High affinity type I interleukin 1 receptor antagonists discovered by screening recombinant peptide libraries.

Abstract: Two families of peptides that specifically bind the extracellular domain of the human type I interleukin 1 (IL-1) receptor were identified from recombinant peptide display libraries. Peptides from one of these families blocked binding of IL-la to the type I IL-1 receptor with IC5o values of 45-140 ,uM. Affinity-selective screening of variants of these peptides produced ligands of much higher affinity (IC50 2 nM). These peptides block IL-1-driven responses in human and monkey cells; they do not bind the human t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 42 publications
1
58
0
1
Order By: Relevance
“…Due to structural stabilization, cyclization of peptide motifs is associated with a higher affinity for the receptors compared with their linear analogues (18,48,50). The design of carrier molecules described in this study may also be applicable for other receptors, such as cytokine or growth factor receptors (48,(51)(52)(53). Studies on drug carriers to the platelet-derived growth factor receptor are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Due to structural stabilization, cyclization of peptide motifs is associated with a higher affinity for the receptors compared with their linear analogues (18,48,50). The design of carrier molecules described in this study may also be applicable for other receptors, such as cytokine or growth factor receptors (48,(51)(52)(53). Studies on drug carriers to the platelet-derived growth factor receptor are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed structure-function analysis of the IL-5͞IL-5 receptor interaction, by scanning alanine mutagenesis of IL-5, has revealed that the key charged residues important for the formation of the ligand-receptor complex are spatially distinct and are separated across a large surface area (17,19). This topography may provide a molecular explanation for the lack of small molecule IL-5 receptor antagonists that have been reported.The screening of libraries of random recombinant peptides has previously led to the discovery of both agonistic and antagonistic peptides to several other cytokine receptors (20)(21)(22). In this study, we report the identification and characterization of two distinct series of specific antagonists of IL-5 that bind to the ligand-binding ␣ subunit of the receptor.…”
mentioning
confidence: 95%
“…The screening of libraries of random recombinant peptides has previously led to the discovery of both agonistic and antagonistic peptides to several other cytokine receptors (20)(21)(22). In this study, we report the identification and characterization of two distinct series of specific antagonists of IL-5 that bind to the ligand-binding ␣ subunit of the receptor.…”
mentioning
confidence: 95%
“…Successful examples of protein minimization projects [4] include the minimization of protein A [5] and atrial natriuretic peptide [6], both to peptides of nearly half the size the original proteins. Even more substantial reductions were recently published by Yanofsky and co-workers [7] who obtained a 15-residue peptide antagonist of the interleukin-1 receptor that may mimic the binding motif of its natural 153-residue antagonist. Wrighton and co-workers [8] reported the discovery of a 20-residue peptide dimer that binds and activates the erythropoietin receptor.…”
mentioning
confidence: 99%